Effect of Toothbrushing Demonstration Method on Students Knowledge of Gingival Recession - Amanda Cahyani; Ita Yulita; Vitri Nurilawaty (Center of Excellent (Pusat Unggulan Iptek), 2026)
Background: Gingival recession is one of the periodontal health problems that can affect oral health and aesthetics. Improper toothbrushing techniques may contribute to the occurrence of gingival recession. Educational interventions, such as counseling using a toothbrushing demonstration method, are expected to improve students’ knowledge regarding the prevention of gingival recession. Objective: To determine the level of knowledge regarding gingival recession before and after counseling using the toothbrushing demonstration method among Grade X students of SMA Yapan Indonesia, Depok City. Method: This study used a pre-experimental design with a one-group pretest–posttest approach. The sample consisted of 65 students selected using a simple random sampling technique. Data were collected using a structured questionnaire to measure students’ knowledge before and after the counseling intervention. Results: Before counseling, the level of students’ knowledge regarding gingival recession was categorized as good (27.7%), moderate (53.8%), and poor (18.5%). After counseling using the toothbrushing demonstration method, the level of knowledge increased, with good (90.8%), moderate (7.7%), and poor (1.5%) categories. Conclusion: Counseling using the toothbrushing demonstration method increased students’ knowledge regarding gingival recession, with knowledge levels improving from predominantly moderate to predominantly good